2022
DOI: 10.2147/ijn.s369373
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Toxicity, and Antibacterial Potential of Gallic Acid-Loaded Graphene Oxide (GAGO) Against Methicillin-Resistant Staphylococcus aureus (MRSA) Strains

Abstract: Background The impetuous usage of antibiotics has led to the perpetual rise of methicillin-resistant Staphylococcus aureus (MRSA), which has garnered the interest of potential drug alternatives, including nanomaterials. Purpose The present study investigates the stability, toxicity, and antibacterial potential of gallic acid-loaded graphene oxide (GAGO) on several MRSA strains. Methods The stability of a synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…We determined the antibacterial activity against Gram-negative E. coli (ATCC 25922) and Gram-positive S.aureus (ATCC 25923, generously supplied by Professor Weihui Wu from the College of Life Sciences, Nankai University) by the Kirby Bauer disk diffusion method. Evenly distributed the bacterial suspension onto LB agar plates, followed by the placement of sterile 6 mm antibiotic disks soaked in 5 mg/mL, 10 mg/mL, 20 mg/mL, 30 mg/mL, 40 mg/mL, and 50 mg/mL MCTH on the plates, incubated at 37 °C for 24 h, and then measured the diameter of the inhibition zones …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined the antibacterial activity against Gram-negative E. coli (ATCC 25922) and Gram-positive S.aureus (ATCC 25923, generously supplied by Professor Weihui Wu from the College of Life Sciences, Nankai University) by the Kirby Bauer disk diffusion method. Evenly distributed the bacterial suspension onto LB agar plates, followed by the placement of sterile 6 mm antibiotic disks soaked in 5 mg/mL, 10 mg/mL, 20 mg/mL, 30 mg/mL, 40 mg/mL, and 50 mg/mL MCTH on the plates, incubated at 37 °C for 24 h, and then measured the diameter of the inhibition zones …”
Section: Methodsmentioning
confidence: 99%
“…Evenly distributed the bacterial suspension onto LB agar plates, followed by the placement of sterile 6 mm antibiotic disks soaked in 5 mg/mL, 10 mg/mL, 20 mg/mL, 30 mg/mL, 40 mg/mL, and 50 mg/mL MCTH on the plates, incubated at 37 °C for 24 h, and then measured the diameter of the inhibition zones. 58 Cell Culture. L929 mouse fibroblast cells were cultured in DMEM (Gibco) supplemented with 1% penicillin and streptomycin (Gibco) and 10% fetal bovine serum (Gibco).…”
Section: Yygggssakpsypptykakpsypptykakpsypptykak-psypptykakpsypptykak...mentioning
confidence: 99%
“…They reported that its efficacy on bacteria at concentrations of ≥150 μg/mL is comparable to cefoxitin. Moreover, this nanoformulation increased the biocompatibility of GA in physiological environments and GAGO had little toxicity in 3T3 murine fibroblast cells and zebrafish embryos cells at all investigated times (24, 48, 72 h) compared to GA alone (Shamsi et al, 2022). Another group of researchers designed liposomes loaded with GA (GA-LIP) and GA-LIP decorated with Lactoferrin (LF-GA-LIP).…”
Section: Antimicrobial Activity Of Ga In Nanoparticle Formulationmentioning
confidence: 99%
“…The results showed the preparation of this nanoformulation significantly increased the antibacterial efficacy of GA against MRSA compared to GA alone. It is suggested that this compound can be a suitable antibacterial agent against multi‐drug‐resistant bacteria (Shamsi et al, 2022 ). Another study showed that the effectiveness of GAGO against MSSA and MRSA was comparable to the first 2 hours of exposure of bacteria to GA and GO alone.…”
Section: Applications Of Ga and Its Derivativesmentioning
confidence: 99%
“…Gallic acid was altered because CNPs can increase antibacterial activity, which is consistent with the findings of previous studies [ 32 ]. Moreover, because of their low toxicity, the previous research utilized gallic acid-loaded graphene oxide against methicillin-resistant Staphylococcus aureus (MRSA) strains, which showed low toxicity of nanocomposites at more than 500 μg/mL for up to 72 h in zebrafish embryos [ 33 ].…”
Section: Introductionmentioning
confidence: 99%